INTEGRATED MODEL OF CITARUM CASCADE RESERVOIR WATER SOURCE MANAGEMENT IN MEETING THE RAW WATER NEEDS AT DOWNSTREAM - Kristianto Ekha S., Wirawan
The Citarum Cascade Reservoir (CCR) is located in the Citarum River Basin, West Java Province, consisting of Saguling, Cirata, and Jatiluhur Reservoir. In general, the function of a reservoir is for hydropower plants, raw water supply, and flood control. Each reservoir has a watershed with its own hydrological regime character and has climate and land conversion problems that are not necessarily the same. CCR management by treating the reservoir only has one hydrological regime causes the discharge of more extreme dry conditions to be unanticipated The purpose of this study is to find a reservoir management conceptual from 1 CCR to 3 integrated reservoirs, using Markov predictions method. This study uses data from year 2009-2018. The mainstay discharge for raw water, also known as dry R5 discharge, is the minimum water discharge that can occur every 5 years once is missed or every 100 years 20 times is missed. Mainstasy discharge is analyzed using the Weibull method with 2 alternative calculations. Alternative 1 is based on historical reservoir inflow dishcarge and alternative 2 is based on upstream reservoir inflow plus local reservoir discharge. While the optimization simulation for reservoir management is based on the economic environment of the reservoir, with a Markov 3 class forecast monthly inflow discharge model with 2 alternative approaches. Alternative 1, based on historical inflow discharge while alternative 2 based on outflow discharge of the upstream reservoir plus the local discharge of each reservoir. As a result, the reservoir mainstay discharge in alternative 2, drier than alternative 1. Mainstay discharge is also less than capacity of West and East Tarum Canal. The optimization simulation of reservoir management in alternative 2 gives results that with Markov forecasts the local monthly discharge reservoir conditions can occur in extreme conditions. In general the reservoir objectives were achieved. The research hypothesis, reservoir mainstay discharge and conceptual management optimization model by treating 1 CCR as 3 integrated reservoirs, one river one management proves that the extreme wet or dry extreme annual discharge conditions of each reservoir affect the results of R5 dry and very dry R10 discharge and reservoir management.